A tailored electrolyte for safe and durable potassium ion batteries. Issue 1 (3rd January 2023) - Fan, Ling; Xie, Huabin; Hu, Yanyao; Caixiang, Zhuoma; Rao, Apparao M.; Zhou, Jiang; Lu, Bingan
Abstract : Electrolytes are critical for the safety and long-term cyclability of potassium ion batteries. Here, a low-concentration, non-flammable, and weakly solvating electrolyte enables the cycling stability of K||graphite cell for over 2 years. Abstract : Electrolytes are critical for the safety and long-term cyclability of potassium ion batteries (PIBs). However, conventional low-concentration electrolytes cannot simultaneously achieve safe and durable PIBs due to their highly flammable solvents or ineffective solid-electrolyte interphase (SEI). Herein, we demonstrate a low-concentration, non-flammable, and weakly solvating electrolyte that simultaneously enhances the safety and cyclability of PIBs. The solvent exhibits non-flammable and weak solvation features, which bolsters the battery safety and the formation of anion-derived SEI even in the low-concentration electrolyte. Specifically, the proposed electrolyte enables a running time of over 200 days and 2 years for K‖Cu and K‖graphite cells, respectively. In addition, the K0.5 MnO2 ‖graphite full cell combined with this proposed electrolyte can operate for 100 cycles with high Coulombic efficiency of 99.7%. This study provides a guiding principle in tailoring electrolytes for achieving safe and long-lasting potassium ion batteries.